Annual trends in follow-up visits for paediatricpediatric concussion in emergency departments and doctors' offices in ontario, canada between 2003–2013. Issue 11 (25th May 2017) - Fridman, Liraz; Scolnik, Michal; Macpherson, Alison; Rothman, Linda; Guttmann, Astrid; Grool, Anne; Rodriguez Duque, Daniel; Zemek, Roger L
Abstract : Background: Over the past ten years, ED and physician office visits for paediatric concussion have more than quadrupled. Current concussion management guidelines recommend follow-upand clearance by a physician prior to resumption of contact activities. However, compliance with recommended follow-up is not well documented in the literature. Objective: To examine trends in follow-up visits in accordance with current recommended guidelines for children with concussion. Design: Retrospective population-based study. Setting: Children and youth presenting to emergency departments (EDs) and doctors' offices with concussion over a 10-year time period (2003–2013) in Ontario, Canada. Outcome measures: We examined the percentage of children and youth who were seen for follow-up visit post-concussion. Trends in the percent of children with a follow-up visit following an index visit to either a doctor's office or an ED were reported. Main results: The proportion of children and youth assessed for concussion follow-up (N=45, 150) has increased significantly (p<0.0001). In 2003, only 1010 of 7170 (14.2%) patients with an index visit for concussion had follow-up assessment; in 2009, 2733 of 10, 134 (27.0%) had a follow-up visit, and by 2013, 11, 806 of 21, 681 (54.5%) received follow-up care. Conclusions: Despite increasing trends in the proportion of children being examined for concussion follow-up over a 10-year period, nearly half of all children with an index visit for concussion still do not receive follow-up assessment. This suggests that ongoing efforts to improve compliance with recommended guidelines will be important. Competing interests: None.